Ludwig Paul (with the Cooperation of Pejman Firoozbakhsh), an Analytical Bibliography of New Iranian Languages and Dialects. Based on Persian Publications Since CA. 1980, Wiesbaden: “Ludwig Reichert Verlag”, 2022, 444 PP. - Artyom Tonoyan; Hakob Avchyan (Banber Arevelagitut'yan Instituti)
Over the past 40-45 years, numerous articles and monographs have been published in Iran, focusing on both Iranian and non-Iranian languages and dialects spoken within the country. During this period, works have also been published in Iran on Iranian languages and dialects spoken outside the country, encompassing regions such as Turkey, Azerbaijan, Afghanistan, Tajikistan, among others. However, a significant portion of the works from both groups does not always capture the attention of non-Iranian researchers. This partial lack of visibility can be attributed to objective factors such as unavailability and language barriers. Additionally, subjective reasons, including a relatively lower interest in scholarly literature published in Iran, contribute to this oversight. One underlying factor for this reality could be a certain viewpoint, regarding the quality of publications in the East (perhaps partially fair in the past, but requiring a completely new approach today), prevalent in Western and Russian academic circles for at least the last two centuries.